2020
DOI: 10.1073/pnas.1913481117
|View full text |Cite|
|
Sign up to set email alerts
|

The histone demethylase JMJD2B regulates endothelial-to-mesenchymal transition

Abstract: Endothelial cells play an important role in maintenance of the vascular system and the repair after injury. Under proinflammatory conditions, endothelial cells can acquire a mesenchymal phenotype by a process named endothelial-to-mesenchymal transition (EndMT), which affects the functional properties of endothelial cells. Here, we investigated the epigenetic control of EndMT. We show that the histone demethylase JMJD2B is induced by EndMT-promoting, proinflammatory, and hypoxic conditions. Silencing of JMJD2B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 63 publications
5
39
0
Order By: Relevance
“…Consistent with the accessibility changes, the corresponding gene expression levels were also increased in ECs exposed to d-flow in E8. These results confirm that d-flow induced EndMT as expected ( Glaser et al, 2020 ; Lai et al, 2018 ; Mahmoud et al, 2017 ; Moonen et al, 2015 ; Ten Dijke et al, 2012 ).…”
Section: Resultssupporting
confidence: 88%
“…Consistent with the accessibility changes, the corresponding gene expression levels were also increased in ECs exposed to d-flow in E8. These results confirm that d-flow induced EndMT as expected ( Glaser et al, 2020 ; Lai et al, 2018 ; Mahmoud et al, 2017 ; Moonen et al, 2015 ; Ten Dijke et al, 2012 ).…”
Section: Resultssupporting
confidence: 88%
“…Consistent with the accessibility changes, the corresponding gene expression levels were also increased in ECs exposed to d-flow in E8. These results confirm that d-flow indeed induced EndMT as expected (Glaser et al, 2020;Lai et al, 2018;Mahmoud et al, 2017;Moonen et al, 2015;Ten Dijke et al, 2012;Warboys et al, 2019).…”
Section: Pseudo-time Trajectory Chromatin Accessibility and Gene Exsupporting
confidence: 86%
“…The critical function of JMJD2B in EndMT was verified in vivo; endothelial specific depletion of JMJD2B in mice resulted in substantial fewer EndMT positive cardiac ECs in the heart after experimentally induced myocardial infarction. However, the reduced EndMT only resulted in a modest rescue of cardiac function 2 weeks after infarction (Glaser et al, 2020).…”
Section: Interplay With Other Signaling Pathways That Mediate or Regumentioning
confidence: 93%
“…Thus, the lack of Stk40 augments the positive function of miR-31 in EndMT (Katsura et al, 2016). Recently, Glaser et al (2020) demonstrated that TGF-β2 as well as a combination of IL-1β/TGF-β1 or hypoxia increased the expression of the histone demethylase Jumonji domain-containing protein 2B (JMJD2B) in HUVECs. Interestingly, both siRNA-mediated silencing and pharmacological inhibition of JMJD2B greatly reduced TGF-β2induced EndMT in HUVECs as demonstrated by a deceased SM22α expression, preserved CDH5 expression and reduced endothelial permeability.…”
Section: Interplay With Other Signaling Pathways That Mediate or Regumentioning
confidence: 99%